Women’s Resistance and the Ideology of Patriarchal Hegemony in Ayu Utami’s Novel Larung: A Critical Discourse Analysis - Suharyo Suharyo; Agus Nuryatin; Subyantoro Subyantoro; Mukh Doyin (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study analyses women's resistance and the ideology of patriarchal hegemony as narrated in Ayu Utami's novel Larung. The main issue raised is the mechanism by which female characters negotiate their identities and build counter-consciousness within a patriarchal social structure, especially after the New Order. The objective of this study is to provide an in-depth explanation of this process. This study employs Norman Fairclough's Critical Discourse Analysis (CDA) framework, integrated with Antonio Gramsci's theory of hegemony, as its analytical basis. This qualitative study utilizes the text Larung as primary data. The analysis is conducted through Fairclough's three-dimensional model, covering text, discourse practice, and sociocultural practice, to comprehensively map the complex relationship between language, ideology, and power. The findings show that women's resistance is manifested through linguistic, narrative, and symbolic strategies, which collectively serve to redefine women's bodies and sexuality as autonomous realms of consciousness and agency. The discourse practices in Utami's work explicitly highlight solidarity among women and offer a sharp critique of patriarchy's limitations. In conclusion, language in literary works is a strategic arena for ideological struggles that enable women to reclaim discursive authority, and the combination of CDA and hegemony theory approaches has proven highly valid for interpreting the dynamics of power and feminist resistance.